Combination of Dissolving Microneedles with Nanosuspension and Co-Grinding for Transdermal Delivery of Ketoprofen - Delly Ramadon; Fathin Ulayya; Annisa Sakinah Qur'ani; Iskandarsyah Iskandarsyah; Yahdiana Harahap; Qonita Kurnia Anjani; Vania Aileen; Pietradewi Hartrianti; Ryan F. Donnelly (MDPI AG, 2023)
Ketoprofen is an anti-inflammatory agent that may cause gastric irritation if administered orally. Dissolving microneedles (DMN) can be a promising strategy to overcome this issue. However, ketoprofen has a low solubility; therefore, it is essential to enhance its solubility using certain methods, namely nanosuspension (NS) and co-grinding (CG). This research aimed to formulate DMN containing ketoprofen-loaded NS and CG. Ketoprofen NS was formulated with poly(vinyl alcohol) (PVA) at concentrations of 0.5%, 1%, and 2%. CG was prepared by grinding ketoprofen with PVA or poly(vinyl pyrrolidone) (PVP) at different drug-polymer ratios. The manufactured ketoprofen-loaded NS and CG were evaluated in terms of their dissolution profile. The most promising formulation from each system was then formulated into microneedles (MNs). The fabricated MNs were assessed in terms of their physical and chemical properties. An in vitro permeation study using Franz diffusion cells was also carried out. The most promising MN-NS and MN-CG formulations were F4-MN-NS (PVA 5%-PVP 10%), F5-MN-NS (PVA 5%-PVP 15%), F8-MN-CG (PVA 5%-PVP 15%), and F11-MN-CG (PVA 7.5%-PVP 15%), respectively. The cumulative amounts of drug permeated after 24 h for F5-MN-NS and F11-MN-CG were 3.88 ± 0.46 µg and 8.73 ± 1.40 µg, respectively. In conclusion, the combination of DMN with nanosuspension or a co-grinding system may be a promising strategy for delivering ketoprofen transdermally.